Bioturbation of peanut worms Sipunculus nudus on the composition of prokaryotic communities in a tidal flat as revealed by 16S rRNA gene sequences. Issue 8 (7th February 2019) - Li, Junwei; Hu, Ruiping; Guo, Yongjian; Chen, Suwen; Xie, Xiaoyong; Qin, Jian G.; Ma, Zhenhua; Zhu, Changbo; Pei, Surui
Abstract: To understand the impacts of peanut worms Sipunculus nudus on the prokaryotic community composition in a tidal flat, an onsite investigation was conducted in Suixi in the Beibu Gulf (109.82E, 21.35N) in the burrow sediments, non‐burrow sediments and the sediments without peanut worm disturbance (control). The16S rRNA gene Illumina MiSeq sequencing was used to investigate the microbial communities and their response to bioturbation by S. nudus in a sandy tidal flat. A total of 18 bacteria phyla were detected, and Proteobacteria and Cyanobacteria constituted the majority of the prokaryotic community in the samples. The distribution of the relative abundances of genera showed that approximately 6.99%–17% of the reads in the samples were classified into 25 known genera. Sulfate‐reducing bacteria ( Desulfococcus and Desulfosarcina ) were the most abundant taxa, followed by Thermodesulfovibrionaceae LCP‐6, indicating that sulfate reduction is the main process in the sandy tidal flat. The abundances of Desulfococcus, LCP‐6 and Cyanobacterium in the non‐burrow sediment were greater than in the burrow sediment, suggesting that the anoxic condition is more suitable for Desulfococcus and LCP‐6 when the activity of S. nudus is absent. The biomass of Cyanobacterium was decreased by the feeding bioturbation of S. nudus . Meanwhile, the relative abundance of the Bacteroidetes Luteimonas in the burrow sediments was significantly greater than in the non‐burrow sediment, and there was a strong relationship between S. nudus bioturbation and increased in oxygen contents and oxidation‐reduction potentials in the burrow sediment. The abundances of Desulfococcus and LCP‐6 were greater in the middle layer (20–30 cm) than in the top layer in the non‐burrow sediment. However, the middle and bottom layers (20–30, 30–40 cm) had higher abundances of these genera than did the upper layers (0–10, 10–20 cm) in the burrow sediments. The abundances of the Fusobacteria Propionigenium and the Spirochaetes Spirochaeta were greater in the middle and bottom layers (20–30 cm, 30–40 cm) than in the top layers (0–10, 10–20 cm) in the burrow sediment, but this phenomenon was not found in the non‐burrow sediment. This study demonstrates that bioturbation by S. nudus plays an important role in reshaping the bacterial community composition in intertidal regions. Abstract : In this study, the microbial community in the sandy tidal flat was different from the other mud tidal flat, while most of the abundant bacterial group were similar. Proteobacteria and Cyanobacteria constitute the majority of the microbial community in the samples, and sulfate reduction and nitrification were the main circulating processes in bottom layers. The microbial community can be affected by the physicochemical characteristics of sediments, which was susceptible to bioturbation of S. nudus .